Participatory creativities: developing a research design for children's pastoral encounters with the natural world. (3rd July 2019) - Saunders, Laura
ABSTRACT: In this paper, the author discusses the interrelationship between creativity, children's experiences of the natural world and pastoral education. Based on a research design developed whilst undertaking a professional doctorate in education (EdD), and grounded in a theoretical framework of children's rights, the author explores the creative uncertainties of collaboratively researching children's educational experiences with nature. The paper considers the ways in which the research design supports a pastoral care agenda, whilst encouraging the emergence of 'creative artefacts', alongside the extent to which the focus of the research, encounters with the natural world, might be deemed pastorally minded in its own right. The children who have participated in the research then draw the paper to a close, sharing what their involvement in the project has meant to them. Images and excerpts of children's own creative reflections are offered as illustration of the powerful confluence of the Creative and the Pastoral.